Polymorphic iconography common influences or individual features in the Near Eastern perspective - First, Grzegorz (BAF-Online: Proceedings of the Berner Altorientalisches Forum, 2025)
Topic: polymorphic iconography in Egyptian religious iconography - special and separate types of mixed, theriomorphic and combined images / icons / forms, always with animal heads, double pairs of wings, phallus, and other magical symbols. Archaeological evidence: images appear on small size flat amulets, papyri fragments (also serving as amulets), bronze statuettes and magical healing statues. Textual evidence: lack of distinctive proper names Place: Egypt, without special area of provenance Date: Late Period (7th – 4th centuries BC), Ptolemaic and Roman Periods (from 4th century BC) Important terms: Pantheistic as an idea of all-embracing god (Pantheos) ba as an emanation / form / manifestation of a god, significantly associated with the image of the god. The animals were ba of gods. bau - strength, power, good and bad at the same time, affecting the whole world, and humans in particular. With the help of magic bau can be manipulated, to ensure people health and success. Deites Bes – Egyptian god – demon, present in magical context, protector of maternity, life, music, safety, with strong solar interpretation, often depicted as a dwarf Tutu (Tithoes) – popular especially as Ptolemaic and Roman Egypt deity; main role was to repel negative powers and to protect people in danger; depicted as sphinx with mixed animal and magical attributes Lamashtu – female Mesopotamian goddess / demon, who preys on mothers and children, depicted in magical context with animal elements Pazuzu – male Babylonian and Assyrian demonic god with rather beneficent, magical role, depicted with animal elements Nine–Shaped (Enneamorfos) – figure present in written Greek Magical Papyri, defined as composed of nine forms, especially of animal origin with magic function and Egyptian genesis Key problem: distribution of polymorphic iconography in other cultures, parallels, influences on the visual level (codification of symbols) and also on the ideological level (magical activity hidden / symbolised in a representation) Question of the talk: to define potential influences in the Near Eastern perspective - is the polymorphic idea specific to one culture or common to all ancient religious thinking about deities?